Reliability of Microtechnology Interconnects, Devices and Systems - Liu, Johan; Salmela, Olli; Sarkka, Jussi; Morris, James E.; Tegehall, Per-Erik; Andersson, Cristina (Springer New York : Imprint: Springer, 2011)
Reliability of Microtechnology discusses the reliability of microtechnology products from the bottom up, beginning with devices and extending to systems. The book's focus includes but is not limited to reliability issues of interconnects, the methodology of reliability concepts and general failure mechanisms. Specific failure modes in solder and conductive adhesives are discussed at great length. Coverage of accelerated testing, component and system level reliability, and reliability design for manufacturability are also described in detail. The book also: Discusses the general failure mechanisms of microsystems on a component level Offers comprehensive coverage of solder joint reliability at the microsystems level Analyzesquality issues and manufacturing at the microsystems level Reliability of Microtechnology is an ideal volume for researchers and professional engineers working in reliability and manufacturing. The book also includes exercises and detailed solutions at the end of each chapter.